2013
DOI: 10.1063/1.4812997
|View full text |Cite
|
Sign up to set email alerts
|

A model of a Serbian energy efficient house for decentralized electricity production

Abstract: This paper presents architectural project and simulation of energy consumption and production of a model of Energy Efficient House for Decentralized Energy (DE). The house model is designed for the area of Serbia, based on the needs of an average Serbian family. The model is designed to investigate opportunities for DE of typical house geometry with advantages of passive solar architecture combined with active solar systems and heat pump. Simulation of the model was performed for the climate conditions for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The paper 7 presents an architectural project that simulates energy consumption and production using a model for an Energy Efficient House for Decentralized Energy (DE). The house model is designed for the area of Serbia, based on the needs of an average Serbian family.…”
Section: Buildingsmentioning
confidence: 99%
“…The paper 7 presents an architectural project that simulates energy consumption and production using a model for an Energy Efficient House for Decentralized Energy (DE). The house model is designed for the area of Serbia, based on the needs of an average Serbian family.…”
Section: Buildingsmentioning
confidence: 99%
“…Installing a PV system of PV modules is also possible on the roofs of individual houses in order to reduce the consumption of electricity for air conditioning and water heating. According to a conducted study [14] it was found that installing a PV system on the roof of the house, with the appropriate inclination of the roof slope and roof orientation, it is possible to reduce the cost of electricity for more than 51% and thus a decentralized model of generating electricity can be achieved.…”
Section: Use Of Solar Energy In Serbiamentioning
confidence: 99%
“…Installing a PV system of solar panels is possible on the roofs of individual houses in order to reduce the consumption of electricity for air conditioning and water heating. According to conducted study [16] it was found that installing a solar system on the roof of the house, with the appropriate level of the roof slope and roof orientation, it is possible to reduce the cost of electricity for more than 51% and thus decentralized model of generating electricity can be achieved. When installing PV modules on the building, By the mid 2012, the company Designing-Engineering center DOMIT Ltd. constructed on its business-industrial building in city of Leskovac, Serbia MSPP.…”
Section: The System Of Mspp Domitmentioning
confidence: 99%